Constructing Children’s Identity: Juvenile Crimes in Singapore News Press in 1950s - Tsai, Evangeline Jia Ying (Nanyang Technological University, 2024)
Many western scholars have discussed the idea of children through the notion of play, labor and education and how they are shaped by all these seemingly positive social cultural norms. On the flip side, juvenile crimes do not fit into this category of positive behavior from children. When one does not fit into a social norm, it becomes a public discourse. As such, this paper will explore the role of news presses covering juvenile crimes particularly, the period right after the Japanese Occupation. The 1950s Singapore is an interesting period as one notes the different groups of people negotiating Singapore self-governance. This paper serves to situate the representation of juvenile crimes in the broader social context that children become a tool of contestation within the English and Chinese news press to negotiate a Singapore identity in the midst of socio-political tensions in the 1950s.